Physiological impact of extracellular vesicles on female reproductive system; highlights to possible restorative effects on female age‐related fertility. (20th February 2019) - Mobarak, Halimeh; Heidarpour, Mohammad; Lolicato, Francesca; Nouri, Mohammad; Rahbarghazi, Reza; Mahdipour, Mahdi
Abstract: An alternative mechanism of cell‐to‐cell communication via extracellular vesicles (EVs) has recently raised increasing attention. EVs are spherical structures comprising exosomes and microvesicles, capable of transferring regulatory molecules and genetic information from one cell to another. EVs act as modulators which can alter a wide spectrum of functions at the cellular level in the recipient cells, taking part in a variety of biological processes in both physiological and pathological conditions. Alteration in EVs content, notably exosomes, was reported during cellular senescence and in patients with age‐related diseases. Most studies reported regulating the impacts of exosomes on fertility and pregnancy outcomes via their capability in carrying developmental signaling molecules like proteins, RNA cargos, influencing gene expressions, affecting growth, and development of embryos during aging. Alterations in the exosomal content and functions can influence the reproductive performance in human and animals as conveyors of senescence signals from outside of the cells. This review aimed to summarize evidence on the role of EVs on modulating fertility, early embryonic development, maternal‐embryo crosstalk for the recognition, and maintenance of pregnancy during maternal aging. Advanced clinical studies are required to strengthen the findings that the benefit of exosomes can be extended to subjects undergoing reproductive aging. © 2019 BioFactors, 45(3):293–303, 2019